Вибір і обґрунтування температурних режимів роботи гідрооб'ємно-механічної трансмісії колісного трактора - Шевцов, Вадим Михайлович (НТУ "ХПІ", 2018)
Дисертація на здобуття наукового ступеня кандидата технічних наук за спеціальністю 05.22.02 – автомобілі та трактори. – Національний технічний університет "Харківський політехнічний інститут", Харків, 2018 р. Дисертацію присвячено підвищенню ефективності використання тракторів з ГОМТ за рахунок визначення впливу температурних режимів роботи ГОП на показники роботи трансмісії, обґрунтуванню параметрів системи охолодження гідрооб'ємної передачі. Проведено аналіз щодо впливу температури робочої рідини на роботу гідросистеми та підходів щодо визначення температурних режимів роботи гідрооб'ємної передачі. Складена розширена матрична математична модель, яка відрізняється урахуванням, окрім кінематичних та силових, температурних режимів роботи ГОП в складі ГОМТ трактора та дозволяє визначити перепад температури робочої рідини на різних ланках гідросистеми в залежності від режимів роботи. Проведені експериментальні дослідження підтвердили адекватність складеної математичної моделі. Проаналізовано характер зміни температури робочої рідини в ГОП на робочих та транспортних передачах. Виявлено залежність загального ККД трансмісії на кожній передачі від температурних режимів роботи ГОП в її складі та сформовані рекомендації щодо методології вибору системи охолодження.

The thesis for granting the scientific degree of Candidate of technical sciences in the specialty 05.22.02 – cars and tractors. – National Technical University "Kharkiv Polytechnic Institute", Kharkiv, 2018. The thesis is devoted to increasing the efficiency of application the tractors based on hydrovolumetric mechanical transmissions (HVMT) through the determination of influence of temperature modes on hydrovolumetric transmission (HVT) characteristics justification of parameters of cooling system in HVT. The influence on temperature of working fluid on the work of hydro system has been carried out. There have been determined the approaches in the determination of temperature modes of HVT. The parameters of cooling system of HVT have been justified. There has been developed the extended mathematical model which considers the temperature, kinematics and power modes of volumetric hydraulic gear in HVMT of the wheel tractor. There also has been developed the mathematic model as a matrix that includes the description of kinematic parameters of HVMT, power parameters and energy conversion efficiency of all gearing parts and thermal characteristics. The provided research approved the adequacy of developed mathematical model. The variation of temperature of working fluid in the working and transport gear may be described as a curve with a maximum in a special zone. There has been determined the influence of temperature on general and volumetric energy conversion efficiency for the each gear and the recommendation for choosing the cooling system that consider the redistribution of power fluids in HVMT were performed.
Choice and substantiation of temperature modes of operation of a hydrovolumetric mechanical transmission of a wheeled tractor
Keywords: колісний трактор; гідрооб'ємно-механічна трансмісія; гідрооб'ємна передача; температура робочої рідини; лабораторний стенд; експериментальні дослідження; дисертації; wheeled tractor; hydrovolumetric mechanical transmissions; hydrovolumetric transmission; working fluid temperature; laboratory unit; experimental researc; 631.372